2011
DOI: 10.1097/wox.0b013e318211496c
|View full text |Cite
|
Sign up to set email alerts
|

World Allergy Organization Guidelines for the Assessment and Management of Anaphylaxis

Abstract: Abstract:The illustrated World Allergy Organization (WAO) Anaphylaxis Guidelines were created in response to absence of global guidelines for anaphylaxis. Uniquely, before they were developed, lack of worldwide availability of essentials for the diagnosis and treatment of anaphylaxis was documented. They incorporate contributions from more than 100 allergy/immunology specialists on 6 continents. Recommendations are based on the best evidence available, supported by references published to the end of December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
1,125
2
135

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 844 publications
(1,276 citation statements)
references
References 148 publications
(133 reference statements)
14
1,125
2
135
Order By: Relevance
“…4). 1, 31, 32, 33 Early injection of adrenaline for anaphylaxis, defined as injection before ER arrival, can significantly reduce the likelihood of hospital admission, as compared with initial injection after arrival at the ER 34. Although no human studies regarding the timing of treatment for anaphylaxis could be found, analysis of 92 deaths related to anaphylaxis showed that adrenaline was given prior to cardiac arrest in only 22 of the cases (24%) 35.…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%
See 4 more Smart Citations
“…4). 1, 31, 32, 33 Early injection of adrenaline for anaphylaxis, defined as injection before ER arrival, can significantly reduce the likelihood of hospital admission, as compared with initial injection after arrival at the ER 34. Although no human studies regarding the timing of treatment for anaphylaxis could be found, analysis of 92 deaths related to anaphylaxis showed that adrenaline was given prior to cardiac arrest in only 22 of the cases (24%) 35.…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%
“…Most international anaphylaxis guidelines recommend injection of adrenaline by the intramuscular route in the mid‐anterolateral thigh at a dose of 0.01 mg/kg of a 1:1,000 (1 mg/mL) solution, up to a maximum of 0.5 mg in adults (0.3 mg in children). Depending on the severity of the episode and the response to the initial injection, the dose can be repeated every 5–15 min, as required 1, 31, 33, 36. Intravenous adrenaline is an option in patients with severe hypotension or cardiac arrest unresponsive to intramuscular doses of adrenaline and fluid resuscitation 1.…”
Section: Initial Treatment Of Anaphylaxismentioning
confidence: 99%
See 3 more Smart Citations